USING PODCASTS FOR ENHANCING LISTENING SKILLS - Mamatqulov Ziyodbek Ilhom o’g’li Teshaboyeva Nafisa Zubaydulla qizi (ZAMONAVIY TA’LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2024)
This article explores the use of podcasts as an innovative tool to enhance listening skills in language learning. Podcasts provide learners with authentic audio materials that expose them to natural language use in various contexts, accents, and topics. The flexibility of podcasts allows learners to listen at their own pace, replay content, and engage with diverse accents, which is especially beneficial in the development of listening comprehension. The article discusses how podcasts can be integrated into classroom instruction, suggesting strategies such as pre-listening activities, guided listening tasks, and post-listening discussions. Furthermore, the article emphasizes the benefits of podcasts in promoting learner autonomy, motivation, and engagement by providing content that is both interesting and educational. Finally, the paper highlights challenges such as technological access and ensuring that podcasts align with the learners’ language proficiency levels.